Chemical and microbiological contamination in limpets (Patella aspera) of the Portuguese coast. (January 2021) - Pedro, S.; Cardoso, C.; Caetano, J.; Mourato, M.; Lourenço, H.M.
Abstract: Coastal production areas can be impacted by anthropogenic contamination from urban, agro-industrial and leisure activities. Some contaminants, such as chemical substances, might also have a telluric origin. Non filter feeding univalve mollusks, such as limpets, which are collected in rocky shores either for sale or for auto-consumption, are very appreciated in Portugal, but have been excluded from provisions on the classification of production areas, although they can present relevant contamination and their human consumption may not be risk-free. Thus, the aim of this study was to assess the microbiological and toxic metal contaminations in limpets ( Patella aspera ) of the Portuguese coast, taking into account the production area and seasonal variation, and comparing their contamination levels with those occurring in the bivalve mollusk indicator species, mussels ( Mytilus edulis ). The risks associated to the consumption of limpet meals were also assessed. For that, microbial total and fecal levels and cadmium, lead and mercury contents in limpets and mussel samples, from three coastal areas over several months, were evaluated based on standard methodologies. Contents of mercury and lead in limpets from the three areas studied, were always below the limits of 0.50 mg kg −1 (ww) and 1.5 mg kg −1 (ww) allowed by the EU, respectively. Regarding cadmium, levels in limpet were always above the limit of 1.0 mg kg −1, reaching about 3.0 mg kg −1 (ww) in some samples. These values probably indicate contamination from telluric origin (soil or rocks) in the coastal studied areas. Results indicated that microbiological contamination of fecal origin was low and in general below the detection level. Contamination levels did not show a clear seasonal pattern. The two mollusk species, limpets and mussels, statistically differed in all contaminants analyzed, being cadmium the most of concern, and always higher in limpets than in mussel samples. So, the potential risk associated with limpet consumption, taking into account the cadmium tolerable weekly intake (TWI), was investigated, being possible to reach a reliable recommendation of less than a monthly meal of limpet (160 g) in the specific case of the evaluated Portuguese coastal production areas. As recreational picking of limpets is common in Portugal, official recommendations of maximum periodic human consumption should be published and enforcement increased in forbidden areas. Graphical abstract: Image 1 Highlights: Human consumption of contaminated limpets can pose serious risks for public health. Toxic metals and E. coli were tested in limpets from three Portuguese coastal areas. Mussels were not adequate as reference indicator species for limpets' contamination. Risk assessment of limpets' human consumption was done due to its high Cd levels. Advisable human limpet consumption is less than a monthly meal of 160 g.